Modelo experimental para estudo de toxicidade do tecido nervoso e de meninges em coelhos utilizando ultrassom para orientar a punção subaracnoidea - Pereira, Ivan Dias Fernandes [UNESP] (2015)
Background: neurological complications after spinal blockade are rare, but when they do occur are potentially devastating. Many animals are used for the study of toxicity of the nervous tissue and meninges. The rabbit has been employed in several studies on neurotoxicity, however, in most of them, the drug was introduced in the subarachnoid space through a catheter implanted chronically. This technique does not reproduce the one used in clinical anesthesia, and therefore can compromise the evaluation of the results. As the puncture of the rabbit is performed where there is still spinal cord, the use of ultrasound as a guide of puncture can avoid the trauma triggered by needle puncture and injection of the solution inside the medullary tissue. Objectives: To evaluate the model for study of toxicity of nervous tissue and meninges using ultrasound to guide the introduction of the needle in the subarachnoid space of rabbits, with the purpose to avoid the injury triggered by the trauma of puncture and by intraneural injection of solutions. Methodology: Forty-five young adult female rabbits were used, from the Genetic Group of Botucatu race, with weights between 3200 and 4400 g and lengths of spinal cord between 34 and 38 cm, supplied by the animal facility of the Botucatu Medical School. The animals were divided into 3 groups (G): G1 subarachnoid puncture, G2 saline solution 0.9% and G3 hyperbaric bupivacaine 0.5%. After intravenous anesthesia with xylazine and ketamine, was performed the approach to the subarachnoid space (Quincke needle 22G 1½) in the intervertebral space between the first and second sacral vertebra, guided by ultrasound. The animals of G2 and G3 received the corresponding solutions in volume of 5μL per centimeter of spinal cord (0.2 mL) and the G1 only the subarachnoid puncture. The sensitivity and motility of the animals were evaluated during 3 days. After this trial period, the animals were sacrificed by ...